OP51 Functional and mental health trajectories predicting dementia incidence: latent class analysis in the english longitudinal study of ageing. (2nd September 2017) - Cadar, D; Davies, H; Llewellyn, D; Batty, GD; Steptoe, A
Abstract : Background: Functional disability and depression might be related to an increased risk of future dementia. We aimed to examine the occurrence of functional disability and depression over an eight-year period and evaluate the predictive role of these changes in dementia incidence. Methods: The data used for these analyses are from 1670 men and women aged 65 and older from the English Longitudinal Study of Ageing (ELSA), an on-going, open, prospective cohort study. Seven waves of data between 2002 and 2014 were analysed. Dementia was determined by doctor-diagnosis combined with a score above the threshold of 3.38 on the Informant Questionnaire on Cognitive Decline in the Elderly. Independent linear growth models with time-invariant covariates and a categorical distal outcome (dementia incidence in 2014) were used to examine whether different trajectories of functional abilities (activities of daily living, ADL; and instrumental activities of daily living, IADL) or depressive symptoms (Centre for Epidemiologic Studies Depression Scale, CES-D) between 2002 and 2010 were predictive of new dementia cases four years later. Results: We identified three independent patterns of functional and depressive symptoms trajectory. Most people showed no functional impairments over time ('class III') in either ADL (86%) or IADL (90%), a small group showed a steep deterioration ('class II') in ADL (5%) and IADL (3%), while the others show a substantial disability in either ADL (9%)or IADL (7%) at baseline with only a slow improvement over time ('class I'). Similarly, most participants (79%) did not experience depressive symptoms during the study period ('class III'), a small group (9%) showed increased depressive symptoms over time ('class II'), while the others (2%) started with depressive symptoms and experienced a minor improvement over time ('class I'). After adjustment for age, sex, education and wealth, relative to participants in 'class III', study members who experienced a sharp deterioration in either measure of functional capabilities or depressive symptoms ('class II') were markedly more likely to be classified with dementia four years later (ADL: Odds Ratio (OR)=3.29 (95% Confidence Intervals (CI) 0.37–6.21); IADL: OR=14.59 (95% CI 2.09–26.09) and CES-D: OR=3.94 (95% CI 1.27–6.61)). Conclusion: Our results showed heterogeneity in all measures of functional abilities or depressive symptoms over time, suggesting that a steeper decline in each of these functions is not necessarily a normative process, but could constitute an early indication of neurodegeneration and pre-clinical symptomatology.